Acceptability of radical consumption policies – Utilising futures consciousness to understand elite preferences. (April 2021) - Ahvenharju, Sanna
Highlights: This paper presents a small n case study of 18 Finnish elite members. The study compares the elite members opinions on strong sustainable consumption policies in the light of their futures consciousness profiles. Their motivations and attitudes have been explored using surveys and interviews. The results provide insight on the role of futures consciousness in relation to individual's interest in supporting new policies and radical policy shifts. The study increases our understanding of the psychological processes behind decision-making and policy choices. Abstract: Future consciousness is typically considered an essential feature of good policy-making and a prerequisite for foresight processes, radical innovations and game-changing shifts in policy. The styles of future thinking have, however, rarely been studied among elite members. This paper presents a small n case study of 18 Finnish elite members. It compares their acceptance of radical policy choices and utilises a new five-dimensional model of futures consciousness to identify potential sources for differences in opinions. The results provide insight on the preferences and motivations related to the participants' interests in supporting new policies and radical policy shifts. The aspects of futures consciousness help in shedding light on the ways the participants approached the issues and what kinds of arguments were used in favour or against new policies: How participants with higher systemic perception were concerned about the suitability of new policy measures to the current system whereas participants with high openness to alternatives were keen to imagine potential new solutions and look for paradigm shifts. This analysis increases our understanding of psychological processes behind decision-making and policy choices. It also gives insight on the question of how new policies should be developed and promoted to gain wide support among different kinds of elite members.